INTEGRATED REPORTING AND VALUE OF ENTITY IN INDONESIA - Bisnis, Apriwandi. Fakultas Ekonomi dan; Putri, Syifaa Azaria; Karlina, Ayu; Lestari, Ema; Khoirunisa, Risa; Purwandari, Faradhila (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study provides an analysis of the development company's annual report with an integrated reporting framework for hot sell companies. The purpose of this study is to provide an overview of the application of integrated reporting to the company's value entity. Secondary data was obtained from the content analysis of the annual report of public companies for 2018-2020 and included in the wholesale index category for the period 2018-2020. The results of this study provide evidence that integrated reporting does not affect the value of the company's entity. This reflects the potential to develop reporting by evaluating the indicators of the business model, strategy and allocation of company resources, the presentation of which does not meet the needs of users of financial statements. In addition, the concept of value of entity used in this study contradicts the concept of assets and equity and even uses the assumption of market value based on the balance sheet date. Thus, research on the relationship between reports integrated with the value of entity needs to consider the right size and materiality. It can be considered for companies to develop integrated reports related to the company's market value by providing information that is absorbed and materiality quickly by investors. This research contributes to the development of integrated reports in Indonesia, especially companies that dominate their activities related to the environment and social.